The glucose/fatty acid cycle 1963-2003: A tribute to Sir Philip Randle - Frayn, K (2003)
Glucose and fatty acids are the major fuels for mammalian metabolism and it is clearly essential that mechanisms exist for mutual co-ordination of their utilization. The glucose-fatty acid cycle, as it was proposed in 1963, describes one set of mechanisms by which carbohydrate and fat metabolism interact. Since that time, the importance of the glucose-fatty acid cycle has been confirmed repeatedly, in particular by elevation of plasma non-esterified fatty acid concentrations and demonstration of an impairment of glucose utilization. Since 1963 further means have been elucidated by which glucose and fatty acids interact. These include stimulation of hepatic glucose output by fatty acids, potentiation of glucose-stimulated insulin secretion by fatty acids, and the cellular mechanism whereby high glucose and insulin concentrations inhibit fatty acid oxidation via malonyl-CoA regulation of carnitine palmitoyltransferase-1. The last of these mechanisms, discovered by Denis McGarry and Daniel Foster in 1977, provides an almost exact complement to the mechanism described in the glucose-fatty acid cycle whereby high concentrations of fatty acids inhibit glucose utilization. These additional discoveries have not detracted from the important of the glucose-fatty acid cycle: rather, they have reinforced the importance of mechanisms whereby glucose and fat can interact.